2010
DOI: 10.1017/s1074070800003412
|View full text |Cite
|
Sign up to set email alerts
|

Limited Access to Conservation: Limited-Resource Farmer Participation in the Conservation Security Program in the Southeast

Abstract: The paper examines the joint adoption of conservation tillage, crop rotations, and soil testing by small and limited-resource farmers in the Southeast. The objectives are to determine the potential eligibility of small farmers for the Conservation Security Program, examine socioeconomic factors affecting adoption, and assess the interdependence between adopting different conservation practices. Results indicate that conservation management, ethnicity, and farm characteristics affect practice adoption. Of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Given the uncertainty of future benefits from investing in conservation practices, in some cases it is optimal to delay adoption until more information about a practice becomes available (Dixit & Pindyck, 1994). Conservation programs may alleviate this uncertainty by providing incentives for farmers to trial conservation practices that allow them to gain first-hand experience and take advantage of complementarities between conservation practices (Bergtold & Molnar, 2010). Conservation practices can be more easily assimilated into production systems where complementary practices are in place.…”
Section: Introductionmentioning
confidence: 99%
“…Given the uncertainty of future benefits from investing in conservation practices, in some cases it is optimal to delay adoption until more information about a practice becomes available (Dixit & Pindyck, 1994). Conservation programs may alleviate this uncertainty by providing incentives for farmers to trial conservation practices that allow them to gain first-hand experience and take advantage of complementarities between conservation practices (Bergtold & Molnar, 2010). Conservation practices can be more easily assimilated into production systems where complementary practices are in place.…”
Section: Introductionmentioning
confidence: 99%
“…Because of low income levels and more limited access to land, equipment, capital, and labor, many traditionally underserved farmers, landowners, and operators of small farms, in general, face considerable constraints to adopting conservation practices (Bergtold and Molnar 2010). For example, Nickerson and Hand (2009) found that in making decisions regarding conservation, limited-resource farmers are more impacted by their finances.…”
mentioning
confidence: 99%
“…In a survey of small and limited-resource farmers in Alabama, Georgia, and Mississippi, Waters (2001) found that a lack of familiarity and "how to" information were barriers to conservation practice adoption. Bergtold and Molnar (2010) found that the vast majority of small and limited-resource farmers in the Southeast did not qualify for the Conservation Security Program (CSP) because it required they adopt three specific conservation practices (i.e., soil testing, crop rotations, and conservation tillage), which were oftentimes incompatible with their farming systems. Furthermore, evidence suggests riparian residential landowners are less knowledgeable about water quality and less willing to implement riparian buffers than agricultural landowners (Armstrong and Stedman 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In several past studies, education was found to be a positive factor in the decision to adopt conservation tillage practices (Shortle and Miranowski 1986, Traoré, Landry, and Amara 1998, Wu and Babcock 1998) and was found to negatively affect adoption in others (Bergtold and Molnar 2010). Fuglie (1999) did not find education to be a significant factor in the decision to adopt NT but found education to significantly affect the adoption of other conservation tillage practices.…”
Section: Resultsmentioning
confidence: 97%